Examining Factors Influencing Consumers’ Participation in Social Media Contests - Apsari, Rinka; Aruan, Daniel Tumpal Hamonangan (International Review of Management and Marketing, 2024)
The study examines factors influencing a consumer’s intention to participate in social media contests, such as brand identification, customer experience, social norms, attitude, and perceived behavioral control. An online self-administered survey through social media was conducted, asking those who have participated in social media contests for the last six months. PLS-SEM analysis showed that the intention to participate in online social contests was primarily influenced by consumers’ positive experiences, followed by brand identification and attitude. In addition, customer experience also significantly affects consumers’ perceived behavioral control. From this study, marketers could gain insights into designing online contests that would generate positive experiences with the contest and the company’s products and services.